Strukturisasi Norma: Pengarusutamaan Gagasan Neoliberal dalam Pembangunan di Negara Pasca-Kolonial (Pengalaman Amerika Latin dan Asia) - Ade Marup Wirasenjaya (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2012)
Neoliberalism has create structurization process in post collonial states. The structurization is not only affecting the state souvereignty, but also shape norms and identity. By using the constructivist’s view of the